Eksekutorial Jaminan Fidusia terhadap Debitur yang Cidera Janji (Wanprestasi) Pasca Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Ryamizard Haritzidane Kasyfi Aditya; Yunanto (CV Rewang Rencang, 2025)
Transactions require costs for each party's needs, and in some cases, significant expenses necessitate additional funding. This additional funding is often obtained through debt agreements. A debt agreement may involve collateral owned by the debtor, which is pledged to the creditor. If the debtor defaults, the collateral can be executed to recover the debt.However, Constitutional Court Decision No. 18 of 2019 amended Article 15 of Law No. 49 of 1999 on Fiduciary Security. Previously, if a debtor defaulted, the creditor had the right to execute the fiduciary collateral by selling the pledged asset. However, the ruling removed the automatic executorial power of fiduciary guarantees. As a result, creditors can no longer execute collateral directly. Instead, they must first submit an execution request to the District Court. This change ensures greater legal oversight and protection for debtors in the execution process